STRUKTUR METAFORA DALAM WACANA NARASI [Methafor Structural in Naration Text] - Aria Bayu Setiaji (Kantor Bahasa Provinsi Maluku, 2018)
This study aims to describe the structure of metaphor in terms of topic elements, elements of image and sense elements in the narrative discourse. The data source in this study was obtained from a book collection of short stories and books on life travel stories in the form of published autobiographical books. The data of this study is an expression of metaphor in the form of phrases. Data collection techniques are done by documentation techniques, reading techniques, and note taking techniques. The results of this study indicate the topic elements in the structure of metaphors in narrative discourse forming five comparative concepts, namely (1) the concept of comparison of nouns, (2) the concept of comparison of nouns, (3) the concept of adjective noun, (4) the concept of adjective comparison -nomina, and (5) the concept of adjective-verb comparison. Image elements found in metaphorical structures include animal image elements, synesthesia image elements, anthropomorphic image elements, and abstract to concrete image elements. In the sense element or similarity point in this study found four similarity point categories, namely (1) the point of independence based on equality, (2) the point of similarity based on the function equation, (3) the point of similarity based on the equation of motion or direction, and (4) point similarity based on the equation of action. Penelitian ini bertujuan mendeskripsikan struktur metafora yang ditinjau dari unsur topik, unsur citra dan unsur sense dalam wacana narasi. Sumber data dalam penelitian ini diperoleh dari buku kumpulan cerpen dan buku kisah perjalanan hidup dalam bentuk buku autobiografi yang telah diterbitkan. Data penelitian ini adalah ungkapan metafora dalam bentuk frasa. Teknik pengumpulan data dilakukan dengan teknik dokumentasi, teknik baca, dan teknik catat. Hasil penelitian ini menunjukkan unsur topik pada struktur metafora dalam wacana narasi membentuk lima konsep perbandingan yaitu (1) konsep perbandingan nomina-nomina, (2) konsep perbandingan nomina-verba, (3) konsep perbandingan nomina-adjektiva, (4) konsep perbandingan adjektiva-nomina, dan (5) konsep perbandingan adjektiva-verba. Unsur citra yang ditemukan dalam struktur metafora meliputi unsur citra hewan, unsur citra sinestesia, unsur citra antropomofik, dan unsur citra abstrak ke konkret. Pada unsur sense atau titik kemiripan dalam penelitian ini ditemukan empat kategori titik kemiripan, yaitu (1) titik kemiripan berdasarkan persamaan sifat, (2) titik kemiripan berdasarkan persamaan fungsi, (3) titik kemiripan berdasarkan persamaan gerak atau arah, dan (4) titik kemiripan berdasarkan persamaan tindakan.